2019
DOI: 10.1089/apc.2019.0055
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of an Effective and Sustainable Antiretroviral Therapy Program in Rural South Africa

Abstract: The delivery of high-quality HIV care in rural settings is a global challenge. Despite the successful expansion of antiretroviral therapy (ART) in Africa, viral load (VL) monitoring and ART adherence are poor, especially in rural communities. This article describes a case study of an ART program in the deeply rural Eastern Cape of South Africa. The Zithulele ART Program initiated five innovations over time: (1) establishing district hospital as the logistical hub for all ART care in a rural district, (2) prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Our study suggests several avenues for future research. Although case studies of differentiated ART delivery models in South Africa suggest effects on improved health outcomes [ 42 ], there is a need to test the comparative effectiveness of CCMDD versus standard clinic ART provision on increased viral load suppression and retention in care, overall and by pick-up point type (e.g., in-clinic, external, smart lockers). Research is also needed to document numbers and types of patients for whom CCMDD is infeasible (e.g., rural patients who do not live near pick-up points or without transportation access).…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests several avenues for future research. Although case studies of differentiated ART delivery models in South Africa suggest effects on improved health outcomes [ 42 ], there is a need to test the comparative effectiveness of CCMDD versus standard clinic ART provision on increased viral load suppression and retention in care, overall and by pick-up point type (e.g., in-clinic, external, smart lockers). Research is also needed to document numbers and types of patients for whom CCMDD is infeasible (e.g., rural patients who do not live near pick-up points or without transportation access).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, viral load testing appears to be a main challenge facing ART sites located in peri-urban and rural areas due to absence of equipment, comparable to studies conducted elsewhere on accessibility to ART services. 45,46,47,48,49,50,51 Similarly, CD4 count reagents were also found to be in short supply across all facilities studied, partly due to the introduction of the treat-all policy which recommends that irrespective of CD4 count level, treatment should be initiated in order to ensure quick and immediate enrolment into ART care. 13 In light of this, national survey to include other sentinel facilities across the 16 regions of Ghana can be done to arrive at a more concrete conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Screening titles and abstracts identi ed 66 studies for full-text examination, of which 32 studies met the inclusion criteria and were included. Bibliography review identi ed two additional studies, making a total of 34 studies included in the review (Figure 1) Twenty-nine of the 34 included studies were conducted in and/or had data collected from sub-Saharan Africa (SSA) countries, including South Africa [21][22][23][24][25][26][27][28][29][30][31],…”
Section: Resultsmentioning
confidence: 99%
“…Of 11 studies from South Africa, four were conducted in Cape Town, reporting relatively high VL coverage of 72-89% [22,[24][25][26]. Other studies were conducted in KwaZulu-Natal [21,30,31], Eastern Cape [23,27] and Gauteng [29], and another study [28] included data from ART patients in nine different provinces across the country. Studies with interventions to improve quality of ART program had a VL coverage of >90% whilst other studies reported a VL range of 25%-81%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation